2015
DOI: 10.17265/1539-8072/2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cognate Words and Interlingual Homographs to Investigate the Cross-Linguistics in Second Language Processing in Iran

Abstract: Various investigations have shown that the native language impacts foreign word recognition and this influence is adapted by the dexterity in the nonnative language. Cognates, words which area like beyond two or additional languages in some fields signify an attention-grabbing, illuminating, and crucial facet of foreign or second language learning and research. Forty-five (males and females) participants have been randomly chosen and participated in the experiment in Islamic Azad University, Zanjan, Iran, in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Daulton's extensive work on English-based loanword cognates in Japanese has shown the considerable potential of using cognates in EFL teaching even though the two languages may not be historically connected (Daulton, 2008(Daulton, , 2010. Gholami et al (2015) suggested that the instruction of the structural similarities between the L1 and L2 lexicon facilitates L2 vocabulary acquisition for Iranian English learners. Baird et al's (2016) study on young bilinguals noted that emergent bilingual children had the advantage in using shared phonology of words and were able to recognize and produce cognates without extensive knowledge of orthography of the words.…”
Section: Introductionmentioning
confidence: 99%
“…Daulton's extensive work on English-based loanword cognates in Japanese has shown the considerable potential of using cognates in EFL teaching even though the two languages may not be historically connected (Daulton, 2008(Daulton, , 2010. Gholami et al (2015) suggested that the instruction of the structural similarities between the L1 and L2 lexicon facilitates L2 vocabulary acquisition for Iranian English learners. Baird et al's (2016) study on young bilinguals noted that emergent bilingual children had the advantage in using shared phonology of words and were able to recognize and produce cognates without extensive knowledge of orthography of the words.…”
Section: Introductionmentioning
confidence: 99%